Exosome-Transmitted miR-128 Targets CCL18 to Inhibit the Proliferation and Metastasis of Urothelial Carcinoma - Shang, Donghao; Liu, Yuting; Chen, Zhenghao (Frontiers in Molecular Biosciences, 2022)
Abstract Objective: To investigate the regulatory function of exosome-transmitted miR-128 and chemokine (C-C motif) ligand 18 (CCL18) on urothelial carcinomas (UCs). Methods: Tumor tissues, paracancerous tissues, and serum were collected from 20 patients with UCs (diagnosed at XXX hospital). CCL18 was detected by immunohistochemistry and ELISA. PCR was used to measure the expression levels of CCL18 and mir-183, miR-128, mir-33a in UCs.We acquired exosomes from mesenchymal stem cells and synthesized exosomes overexpressing miR-128 (HMSC-128-EV). The effects of miR-128 on the migration and invasion abilities, apoptosis and epithelial-mesenchymal transition (EMT) of BUC T24 cells were investigated by co-culturing HMSC-128-EV. The therapeutic potential of miR-128 on disease models was explored by injecting HMSC-128-EV into nude mice. Results: The expression of CCL18 in UCs was significantly higher than that in normal tissues (P < 0.05)，and the serum level of CCL18 in patients with UC was significantly increased comared with those in healthy controls (P < 0.05). CCL18 overexpression or downregulation enhanced or suppressed the proliferation and migration of BUC T24 cells, resectively (P < 0.05). The exosome-transmitted miR-128 can inhibit cell proliferation (P < 0.05), invasion (P < 0.05), and migration (P < 0.05) in UCs, and these effects can be reversed by CCL18. In terms of apoptosis, miR-128 was able to promote the occurrence of BUC T24 apoptosis (P<0.05), which can also be reversed by CCL18. In addition, miR-128 can inhibit the proliferation (P < 0.05) and metastasis (P < 0.05) of UCs in nude mice. Conclusion: The miR-128 inhibits the proliferation, invasion, migration of UCs, and promotes its apoptosis by regulating CCL18 secretion.